Increasing leaching rate of gold cyanide of two-stage calcination generated from refractory ore containing arsenopyrite and pyrrhotite - Dang, Xiao-E; Ke, Wen-Shuai; Tang, Chen; Lv, Jun; Zhou, Xue; Liu, Cheng-Peng (Rare metals, 2016)
For the gold locked within hematite in the two- stage calcination, which leads to a low gold leaching rate, the present work is aiming at pretreating the calcination to selectively dissolve hematite. The calcination was pre- treated by sulfuric acid with cosolvent B. The factors in- fluencing the hematite dissolution rate were studied, and the pretreatment parameters considered were H2SO4 con- tent, B dosage and added time, leaching temperature and time. Simultaneously, mineralogy analysis of the calcination, H2SO4 pretreatment residue and cyanide leaching residue were also carried out. Results indicate that the hematite dissolution rate is quicker, the dissolution tem- perature is lower and the dissolution time is shorter in the role of cosolvent B than without B. At the same time, the gold locked within hematite is effectively released, so the leaching rate of gold cyanide increases about 10 % than that in actual factory production. The results have an actual significance in guiding industrial production.